Local Anaesthesia in Dentistry - Baart, Jacques A.; Brand, Henk S. (Springer International Publishing : Imprint: Springer, 2017)
This book, richly illustrated in full colour, is a comprehensive guide to the use of local anaesthesia in dentistry that will meet the needs of both students and dental practitioners. It provides the reader with ample background information on the origin of pain and the pharmacology of anaesthetics, and describes the anatomy of the trigeminal nerve in detail. Subsequent chapters cover key are as such as general practical aspects, local anaesthesia in the upper and the lower jaw, the use of local anaesthetics in children, local and systematic complications, and the prevention of side effects. Patients at particular risk of adverse effects are identified and attention drawn to significant legal aspects. This second edition has been completely revised, with more attention to safety, environment, and sterility. Additional injection techniques have been included, and a new chapter is devoted to microprocessor-assisted administration of anaesthetics. Throughout, care has been taken to ensure that the information is clearly presented and the text is easy to read. .
Keywords: Dentistry.; Pharmacology.; Anesthesiology.; Oral surgery.; Maxillofacial surgery.; elektronické knihy; electronic books